A behavioural economics approach to assessing formation of financial literacy: a conceptual framework / Yong Chen Chen and Muhammad Aizat Zainal Alam - Yong, Chen Chen; Zainal Alam, Muhammad Aizat (2021)
The importance of a financially secure population in a nation has been emphasised worldwide numerous times regardless of the economic conditions of individual countries. Financially literate individuals have proven to be much empowered, independent, and demonstrated higher financial wellbeing. While the importance is obvious, scholars have wide-ranging views in defining and conceptualising financial literacy, which made empirical studies surrounding financial literacy generating contradicting results. Building on the Theory of Planned Behaviour, the current paper proposes a conceptual model to fulfil the paucity of a sound model to understand how financial literacy is formed in an individual. Deriving insights from previous studies, the proposed conceptual model perceives financial literacy as a process consisting of knowledge dimension and application dimension. Two paths were proposed considering the direct and indirect relationships between financial knowledge and financial behaviour, i.e., through attitude and personality of an individual. Standing as an applied behavioural model anchoring on the Theory of Planned Behaviour, the proposed conceptual model explains how financial literacy is formed within an individual. Future researchers are invited to use the conceptual model by adding context-specific variables since the proposed model only provides a general view on the phenomena supporting the argument that decisions are primarily made at an individual level where individual choices and circumstances influence decisions.